Stylistic Transformation Signals in Arabic Grammatical Discourse: A Grammatical- Rhetorical Approach - Abubkr, Lutfi Omar; Al Kaabi, Mozah H.; Almaamari, Hayam; Haidara, Nabeeha Bin (Journal of Ecohumanism, 2024)
This study aims to better understand Arabic grammar and its rhetorical meanings as an integrated system where structure and semantics interact, moving away from rigid interpretations that confine grammar within a formal framework. Through examining Quranic discourse and poetic evidence, the study examines the impact of stylistic transformations on Arabic grammatical analysis to demonstrate how grammatical structure adapts to context and the rhetorical purpose the speaker intends to convey. The study analytically discusses the views of Arabic grammar pioneers, such as Sibawayh, Ibn Hisham, and Ibn Al-Anbari, highlighting their interpretation of stylistic transformations and their significant indicators and whether these phenomena represent exceptions or an expression of language flexibility and its ability to transcend traditional rules. The research also shows examples of rhetorical purposes such as praise, dispraise, specification, and enticement, where the influence of style is reflected in directing grammatical analysis and expanding its connotations. The study reveals the depth of the relationship between style and grammar and its associated rhetorical and semiotic aspects and how these transformations shape the meanings of discourses and enrich their connotations. The study also seeks to stimulate discussion about the discourse of renewal in studying Arabic grammar and its meanings and to link stylistic phenomena signals with modern linguistic analysis that addresses local and global mindsets. Additionally, the study highlights the applications of stylistic transformations in multiple fields, such as Arabic language teaching and the development of Artificial Intelligence (AI) techniques and Natural Language Processing (NLP), making it a vital field for modern applications that combine linguistic heritage with contemporary innovation.